2008
DOI: 10.1158/1535-7163.mct-08-0508
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity and molecular effects of the novel heat shock protein 90 inhibitor, IPI-504, in pancreatic cancer

Abstract: Targeting Hsp90 is an attractive strategy for anticancer therapy because the diversity and relevance of biological processes are regulated by these proteins in most cancers. However, the role and mode of action of Hsp90 inhibitors in pancreatic cancer has not been studied. This study aimed to assess the antitumor activity of the Hsp90 inhibitor, IPI-504, in pancreatic cancer and to determine the biological effects of the agent. In vitro, we show that pharmacologic inhibition of Hsp90 by IPI-504 exerts antiprol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 47 publications
3
60
0
1
Order By: Relevance
“…Despite the large number of inhibitormodulated hits obtained by Sharma et al, surprisingly few of the proteins identified by previous proteomic surveys [25][26][27][28] were reproduced in this new study. Comparison of the proteins the levels of which were changed by more than 1.5-fold revealed that only 8 of the 23 detected by Maloney et al, 25 9 of the 97 found by Schumacher et al, 26 5 of the 34 from Song et al 27 and 3 of the 87 from Yao et al 28 were also present in the Sharma et al catalog.…”
Section: Comparisons and Interpretationmentioning
confidence: 61%
See 2 more Smart Citations
“…Despite the large number of inhibitormodulated hits obtained by Sharma et al, surprisingly few of the proteins identified by previous proteomic surveys [25][26][27][28] were reproduced in this new study. Comparison of the proteins the levels of which were changed by more than 1.5-fold revealed that only 8 of the 23 detected by Maloney et al, 25 9 of the 97 found by Schumacher et al, 26 5 of the 34 from Song et al 27 and 3 of the 87 from Yao et al 28 were also present in the Sharma et al catalog.…”
Section: Comparisons and Interpretationmentioning
confidence: 61%
“…Comparison of the proteins the levels of which were changed by more than 1.5-fold revealed that only 8 of the 23 detected by Maloney et al, 25 9 of the 97 found by Schumacher et al, 26 5 of the 34 from Song et al 27 and 3 of the 87 from Yao et al 28 were also present in the Sharma et al catalog. No proteins were common to more than 3 of the 5 studies.…”
Section: Comparisons and Interpretationmentioning
confidence: 89%
See 1 more Smart Citation
“…The biological and anti-neoplastic effects of IPI-504 have been demonstrated in multiple in vitro and in vivo models of cancer (Bauer et al, 2006;Peng et al, 2007;Dewaele et al, 2008;Song et al, 2008;Leow et al, 2009) leading to its clinical development in various phase 2 studies (clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…IPI-504 has been found to display antitumor activity against pancreatic cancer xenografts and is a promising compound against gastrointestinal stromal tumors of platelet-derived growth factor receptor-a mutants. 50 Genistein, an isoflavone, inhibits EGFR tyrosine kinase, 51 and also inhibits the Hsp90 deacetylase (HDAC6)-Hsp90 co-chaperone function, which downregulates the expression of androgen receptor in androgen-dependent prostate cancer cell lines. 52 Quercetin, a flavonoid, inhibits cancer cells that over-express ErbB2 (Her-2/neu) trans-membrane tyrosine kinase and downregulates the downstream PI3K-Akt signaling pathway.…”
Section: Actions Ofmentioning
confidence: 99%